PENGGUNAAN SINAR UV DAN HIDROGEN PEROKSIDA UNTUK MENURUNKAN COD, TSS DAN TDS AIR BUANGAN PABRIK OLEOKIMIA - Lina Chuango; Chairudin -; Tini Sembiring (Saintia Kimia, 2013)
Oleochemical plant wastewater contain organic material in high concentration. These organic materials will pollute the environment if discharged directly. The aim of the research is to determine the effect of the UV light, hydrogen peroxide and the combination of UV-hydrogen peroxide to reduce the levels of organic material in the outlet of wastewater plant of Oleochemical. The observed variables are COD, TDS and TSS associated with the exposure time range at 15, 30, 45 and 60 minutes and the amount of addition of hydrogen peroxide at 25, 20, 75 and 100 mL. The results of analysis show that the addition of100 mLof hydrogenperoxideisthe mosteffectivebecause it canreduce theCOD, TDSandTSS are55.0%, 51.9%, and28.8% respectively. Whiletreatmentwith the use ofUV lightanda combination ofUV-hydrogen peroxidecan reduce theCODby62.6% and 76.7%; TSSby40.1% and 46.2%; but increase theTDSby17.82% and 59.2%. Keywords : UV/ H2O2, TDS,COD, TSS, Oleochemical Wastewater